Diskursus Islam Liberal; Strategi, Problematika dan Identitas - Saifuddin Dhuhri (Media Syari'ah, 2012)
This article sheds light on thoughts of the Liberal Islam proponents concerning to the way they view about the Islamic law application in Aceh. In doing so, it explains the strategies that liberal Islam takes to disseminate their beliefs among Moslems and then how their positions are criticised among western thinkers in the post modern era. The second part of this work will elucidate their views on the Acehnese Sharia and the way their opinions are countered by traditionalists. Finally, this article will offer some possible solutions for dealing with the divergents of Islamic thought that leads to cultural conflict. The discussion will eventually bring the method of Freire’s conscientizacao as the way out from the cultural conflict.